LEGAL BASIS OF EXHIBITIONS’ AND TRADE FAIRS’ ORGANIZATION - Andrey A. Kirillovykh (Сравнительная политика, 2015)
The article deals with the main aims of exhibitions and trade fairs and essential organizational differences between them. The exhibitions and trade fairs are understood as market activities at which goods, services and (or) information are demonstrated and spread and which are organized at fixed and regular intervals. Russia lacks single legislation in the sphere of exhibitions. Turning to the pre-revolutionary experience of exhibition the article concludes that noncommercial partnership could be the most suitable legal form for exhibitions